Programming plans and programming techniques - Bowles, A.; Brna, Paul (1993)
Abstract: "The notion of programming plans has been used in helping students learn how to program (Bonar & Cunningham, 1988; Gegg- Harrison, 1991). We argue that the notion of programming plans is too diffuse and idea to provide detailed support for novices. In contrast, the notion of programming techniques provides a better basis upon which to build (Brna et al, 1991). We describe and motivate a set of common Prolog programming techniques in detail. The techniques cover most of the constructs seen in simple Prolog predicates, and we believe represent a useful level of abstraction for describing and adapting Prolog programs."
Keywords: Bionics and artificial intelligence; Computer software; Computer-assisted instruction